2019
DOI: 10.1049/iet-spr.2018.5032
|View full text |Cite
|
Sign up to set email alerts
|

Sleep stages classification from EEG signal based on Stockwell transform

Abstract: Sleep has great effect on physical health and quality of life. Electroencephalogram (EEG) signal is used in studying sleep process and recently, time-frequency transforms are increasingly utilised in EEG signal analysis. This study proposes an efficient method for sleep stages classification based on a time-frequency transform, namely Stockwell transform. In the introduced method, at first, the Stockwell transform is used to map each 30 s epoch of EEG signal into the time-frequency domains, which results in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 51 publications
1
13
0
Order By: Relevance
“…Lee et al [34] have suggested the Pz-Oz EEG for feature extraction behaved better than the Fpz-Cz in fatigue detection, which provided approximately 69% of the total features. Ghasemzadeh et al [35] have used the Fpz-Cz and Pz-Oz EEGs for sleep staging, and their result indicates that the accuracy of the Fpz-Cz EEG is higher than the Pz-Oz. In this study, we found no significant difference in the 2 stages between the Fpz-Cz group and the Pz-Oz group by the WLMF method.…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al [34] have suggested the Pz-Oz EEG for feature extraction behaved better than the Fpz-Cz in fatigue detection, which provided approximately 69% of the total features. Ghasemzadeh et al [35] have used the Fpz-Cz and Pz-Oz EEGs for sleep staging, and their result indicates that the accuracy of the Fpz-Cz EEG is higher than the Pz-Oz. In this study, we found no significant difference in the 2 stages between the Fpz-Cz group and the Pz-Oz group by the WLMF method.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies on the division of EEG frequency bands have been performed [28][29][30][31][32]. Additionally to the common five sub-band division methods of delta, theta, alpha, beta and gamma, according to previous studies, the alpha band can be divided into two parts (8-10 Hz and 10-13 Hz) [28], the beta band can be divided into two parts (13-18 Hz and 18-30 Hz) [29] [30]or three parts (13-18 Hz,18-25 Hz and 18-30 Hz) [31] and the gamma band can be divided into two parts (30-40 Hz and 40-49.5 Hz) [30] or four parts (30)(31)(32)(33)(34)(35)(36)(36)(37)(38)(39)(40) Hz, 40-46 Hz and 46-49.5 Hz) [32]. In this study, according to the above frequency band division methods, different frequency partitioning schemes for EEG signals were used and 5, 7, 9 and 11 frequency sub-bands were obtained, respectively.…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…where t and f are, respectively, the spectral localization time and Fourier frequency, and g(t) represents the window function. The following Gaussian function (g(t)) is used in the above equation to evaluate the Stockwell Transform-based decomposition of i(t) [30].…”
Section: Stockwell Transform-based Median and Summation Indexmentioning
confidence: 99%